Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Shibori dan Pemasaran dalam Upaya Meningkatkan Kesejahteraan Ekonomi Keluarga di Kampung Ringintelu Ngaliyan Semarang - Masitha Fahmi Wardhani; Diana Puspitasari; Amalia Nur Chasanah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Ringintelu Village, which is located in Kalipancur Village, Ngaliyan District, Semarang City, has a strategic and potential location. Located near the tourist area of the River Tubing Mayangsari and the historical monument Tugu Suharto with easy road access and busy road activity from the Sam Poo Kong tourist road and Kreo Cave to the Gajahmungkur-Gunung Pati area, which is a hilly area of many public and private universities in Semarang City. In the field, it can be seen that the productivity of the surrounding community has not seen the potential of this area to be used as an attraction to come. One of the solutions starts with mobilizing housewives by providing knowledge and skills through shibori and marketing training, as well as solutions for dealing with the effects of post-pandemic conditions by increasing productivity to advance the welfare and economy of local regional families. Increasing business competition is currently being addressed by developing creative business ideas by providing business insights to housewives to remain productive and have additional income. This Community Partnership Program activity uses counseling and training methods related to the importance of having the skills to make creative products, namely shibori bags that are ready to sell, as well as knowledge of marketing in the